Estimating Risk of Cardiovascular Disease Among Long-Term Colorectal Cancer Survivors: A Nationwide Cohort Study - Jeong, Seogsong; Lee, Gyeongsil; Choi, Seulggie; Kim, Kyae Hyung; Chang, Jooyoung; Kim, Sung Min; Kim, Kyuwoong; Son, Joung Sik; Cho, Yoosun; Park, Sang Min (Frontiers in Cardiovascular Medicine, 2022)
Background: Growing number of colorectal cancer survivors has emerged concerns regarding cardiovascular disease (CVD) risks. However, there is yet a predictive tool that is estimative of CVD risks and supportive for management of healthcare as well as disease prevention in terms of CVD risks among long-term colorectal cancer survivors. Aim: To develop predictive tools to estimate individualized overall and each subtype of CVD risks using a nationwide cohort in South Korea. Methods and Results: A total of 4709 newly diagnosed patients with colorectal cancer who survived at least 5 years in the National Health Insurance System were analyzed. Cox proportional hazards regression was used for identification of independent risk factors for derivation of predictive nomograms, which were validated in an independent cohort (n=3957). Age, fasting serum glucose, γ-glutamyl transpeptidase, Charlson comorbidity index, household income, body mass index, history of chemotherapy, cigarette smoking, and alcohol consumption were identified as independent risk factors for either overall CVD or each subtype of CVD subtype. Based on the identified independent risk factors, 6 independent nomograms for each CVD category were developed. Validation by an independent cohort demonstrated a good calibration with a median C-index of 0.687. According to the nomogram-derived median score, relative risks of 2.643, 1.821, 4.656, 2.629, 4.248, and 5.994 were found for overall CVD, ischemic heart disease, myocardial infarction, total stroke, ischemic stroke, and hemorrhage stroke in the validation cohort. Conclusions: The predictive tools were developed with satisfactory accuracy. The derived nomograms may support estimation of overall and each CVD risks for long-term colorectal cancer survivors.